Existence and Extendability of Solutions of the Equation g(t, x) = 0 - Kaplun, Yu. I.; Samoilenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider the problem of extendability and existence of solutions of the equation g(t, x) = 0 on the maximum interval of their definition.